The Invention of religion: faith and covenant in the Book of Exodus - Assmann, Jan (Princeton University Press, 2018)
Frontmatter -- CONTENTS -- Illustrations -- Foreword -- Introduction -- PART ONE. GENERAL FOUNDATIONS -- CHAPTER ONE. Theme and Structure of the Book of Exodus -- CHAPTER TWO. The Historical Background: Event and Remembrance -- CHAPTER THREE. Textual History and the History of Meaning -- PART TWO. THE EXODUS -- CHAPTER FOUR. The Tribulations of the Israelites and the Birth of the Savior -- CHAPTER FIVE. God Reveals His Name: Moses at the Burning Bush -- CHAPTER SIX. Signs and Wonders: God Reveals His Power -- PART THREE. THE COVENANT -- CHAPTER SEVEN. The Calling of the People -- CHAPTER EIGHT. Treaty and Law -- CHAPTER NINE. Resistance Moses and the Violent Fate of the Prophets -- CHAPTER TEN. The Institutionalization of Divine Presence -- Conclusion -- Notes -- Bibliography -- Illustration Credits -- Index